The Effects of Changes of the Job Offer Arrival Rate on the Duration of Unemployment - van den Berg, Gerard J. (Journal of Labor Economics, 1994)
Generally, it is acknowledged that changing the job-offer arrival rate has two opposite effects on unemployment duration. For a basic job search model, sufficient conditions on the wage-offer distribution have been derived, ensuring that one of the effects dominates. However, these are not satisfied for the popular families of wage-offer distributions. Here the author shows that the conditions can be weakened at virtually no cost. The set of distributions satisfying the new conditions is considerably larger than the set previously established. In particular, it includes all wage-offer distribution families that are popular in structural empirical research. Copyright 1994 by University of Chicago Press.